2017
DOI: 10.1016/j.bpj.2016.11.1456
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoaccumulative Elements of the Mammalian Actin Cytoskeleton

Abstract: To change shape, divide, form junctions, and migrate, cells reorganize their cytoskeletons in response to changing mechanical environments [ 1 -4 ]. Actin cytoskeletal elements, including myosin II motors and actin crosslinkers, structurally remodel and activate signaling pathways in response to imposed stresses [5][6][7][8][9]. Recent studies demonstrate the importance of force-dependent structural rearrangement of α-catenin in adherens junctions [ 10 ] and vinculin's molecular clutch mechanism in focal adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…Previous studies put forward that the actin cross-linker α-actinin-4 forms catch bonds: Yao et al showed stressenhanced gelation of in vitro actin networks cross-linked by α-actinin-4 indicating catch bond behaviour. Previous studies with Dictyostelium cells demonstrated slowed α-actinin-4 turnover in the actin cytoskeleton in response to compressive stress 6 and accumulation of α-actinin-4 in response to suction pressure from micropipette aspiration 7 . However, to date, there is no study that showed a quantitative relation between α-actinin-4 cross-linking lifetimes and mechanical tension in the cytoskeleton.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies put forward that the actin cross-linker α-actinin-4 forms catch bonds: Yao et al showed stressenhanced gelation of in vitro actin networks cross-linked by α-actinin-4 indicating catch bond behaviour. Previous studies with Dictyostelium cells demonstrated slowed α-actinin-4 turnover in the actin cytoskeleton in response to compressive stress 6 and accumulation of α-actinin-4 in response to suction pressure from micropipette aspiration 7 . However, to date, there is no study that showed a quantitative relation between α-actinin-4 cross-linking lifetimes and mechanical tension in the cytoskeleton.…”
Section: Introductionmentioning
confidence: 93%
“…3 A). Similarly, the actin cross-linking protein filamin can accumulate in response to shear stress in multiple cell types (18,49). However, the mammalian paralog filamin B shows higher mechanosensitive accumulation than filamin A (Fig.…”
Section: Force Sensing By Other Actin-associated Proteinsmentioning
confidence: 98%
“…At higher forces, these bonds then slip so that they display a catch-slip behavior, depending on the force regime. The catch-slip bond also accounts for the mechanosensitive accumulation (the accumulation of a protein in response to applied stress) of the actin cross-linking protein a-actinin (18,49) and its recruitment to focal adhesions under high tension (50). In mammalian cells, mechanoaccumulation is unique to the a-actinin 4 paralog, and is not observed for a-actinin 1 (49) (Fig.…”
Section: Force Sensing By Other Actin-associated Proteinsmentioning
confidence: 99%
See 2 more Smart Citations